Teaching and Learning Biological Evolution (be) with the Theoretical Persective of Conceptual Profile: Implications for Teachers’ Continuous Training (2016)
This paper aims to present an educational alternative called conceptual profile in continuing training of science teachers, whose goal is to improve teaching and learning of science concepts. The concept developed from this perspective is the teaching of biological evolution. For this purpose this dissertation develops four key points: (1) theoretical and methodological of conceptual profile theory aspects are discussed; (2) the characteristics that allow talking about relevance of biological evolution concept for building of a conceptual profile are presented; (3) methodological aspects are proposed through a construction route of three dimensions of the biological evolution conceptual profile, namely, socio-cultural, ontogenetic and microgenetic dimensions, which, dialogically, establish a conceptual profile of biological evolution that generate an explanatory model for understanding thought and language in science classroom around the concept itself; (4) as a conclusion, the importance of relations between this educational alternative and some aspects of the continuous training of teachers becomes evident.